Technology and Communication: An Analysis of Digital Communication Skills of Teachers and Parents - Nurjanah, Novita Eka; Rasmani, Upik Elok Endang; Jumiatmoko, Jumiatmoko; Fitrianingtyas, Anjar; Zuhro, Nurul Shofiatin (Program Studi Magister Pendidikan Anak Usia Dini, 2026)
The convenience of use and rapid advancement of digital technology across various sectors have created an environment where communication between teachers and parents takes place through digital applications. Although digital technology opens up new opportunities for improving the effectiveness of communication, studies that specifically explore the use of digital technology in the context of early childhood education in Indonesia remain limited. The purpose of this study was to obtain data on early childhood teachers' views on digital technology used in communicating with parents and the extent to which digital technology can facilitate meaningful communication between teachers and parents. This study applied a quantitative approach with a cross-sectional survey design through the distribution of online questionnaires using Google Forms, which were then analyzed using descriptive statistical techniques and the System Usability Scale (SUS) instrument. The respondents in the study were 120 early childhood education teachers. The results show that early childhood teachers in Indonesia generally have adequate academic qualifications and professional certifications and actively utilize digital technology, particularly WhatsApp and Google Meet, to strengthen interactive communication with parents, which has proven to be effective, easy to use, and contributes significantly to enhancing collaboration in supporting early childhood development. Recommendations for further studies are expected to analyze the long-term impact of digital technology utilization on the quality of teacher-parent relationships, parent involvement, and child development outcomes, not only in terms of communication.